Dexpramipexole enhances hippocampal synaptic plasticity and memory in the rat. (December 2018) - Coppi, Elisabetta; Lana, Daniele; Cherchi, Federica; Fusco, Irene; Buonvicino, Daniela; Urru, Matteo; Ranieri, Giuseppe; Muzzi, Mirko; Iovino, Ludovica; Giovannini, Maria Grazia; Pugliese, Anna Maria; Chiarugi, Alberto
Abstract: Even though pharmacological approaches able to counteract age-dependent cognitive impairment have been highly investigated, drugs improving cognition and memory are still an unmet need. It has been hypothesized that sustaining energy dynamics within the aged hippocampus can boost memory storage by sustaining synaptic functioning and long term potentiation (LTP). Dexpramipexole (DEX) is the first-in-class compound able to sustain neuronal bioenergetics by interacting with mitochondrial F1Fo-ATP synthase. In the present study, for the first time we evaluated the effects of DEX on synaptic fatigue, LTP induction, learning and memory retention. We report that DEX improved LTP maintenance in CA1 neurons of acute hippocampal slices from aged but not young rats. However, we found no evidence that DEX counteracted two classic parameters of synaptic fatigue such as fEPSP reduction or the train area during the high frequency stimulation adopted to induce LTP. Interestingly, patch-clamp recordings in rat hippocampal neurons revealed that DEX dose-dependently inhibited (IC50 814 nM) the IA current, a rapidly-inactivating K + current that negatively regulates neuronal excitability as well as cognition and memory processes. In keeping with this, DEX counteracted both scopolamine-induced spatial memory loss in rats challenged in Morris Water Maze test and memory retention in rats undergoing Novel Object Recognition. Overall, the present study discloses the ability of DEX to boost hippocampal synaptic plasticity, learning and memory. In light of the good safety profile of DEX in humans, our findings may have a realistic translational potential to treatment of cognitive disorders. Highlights: DEX, the enantiomer of the antiparkinsonian drug pramipexole, enhances LTP in hippocampal slices isolated from aged but not young rats. DEX effect is not related to increased bioenergetics, as expected from our previous study (Muzzi et al., Br J Pharmacol. 2018; 175(2):272–283). DEX dose-dependently inhibits transient outward K + current in isolated hippocampal neurons identified as IA current. DEX counteracts scopolamine-induced spatial memory impairment in the in vivo Morris water maze test.